IMPLEMENTASI E-GOVERNMENT UNTUK MENINGKATKAN KUALITAS LAYANAN PUBLIK DI KABUPATEN BANYUWANGI - Al'libani, Ridha Rahim; Prayoga, Indra Aditya; Priatna, Ami; Munawaroh, Fitri Mustika Madliah (Jurnal Progress Administrasi Publik, 2025)
This study explores the implementation of electronic government (e-government) in Banyuwangi Regency, Indonesia, as a strategy to enhance the quality of public services. Although progress has been made, local governments still encounter challenges such as infrastructure limitations, gaps in digital literacy, and bureaucratic resistance. Employing a mixed methods approach, the research analyzes survey data from 210 respondents and in-depth interviews with civil servants and citizens. The results indicate that high levels of technology acceptance, reflected in perceptions of usefulness and ease of use, contribute positively to service quality dimensions including reliability, responsiveness, and assurance. Political support, digital innovation, and citizen involvement emerge as key enabling factors, while infrastructure disparities and unequal digital competencies remain persistent barriers. This study contributes theoretically by integrating the Technology Acceptance Model (TAM) with SERVQUAL and offers practical insights for developing inclusive digital governance strategies.   Keywords: E-Government; Public Innovation; Service Quality; Technology Acceptance.